2018
DOI: 10.1159/000488407
|View full text |Cite
|
Sign up to set email alerts
|

The Antimuscarinic Agent Tolterodine Regulates Bladder Extracellular Matrix in Partial Bladder Outlet Obstruction in Rats

Abstract: Background/Aims: Antimuscarinic agents can delay the progression of bladder dysfunction caused by bladder outlet obstruction (BOO). To date, the relationship between muscarinic receptor activity and the bladder extracellular matrix (ECM) remains unclear. Thus, an animal model of partial BOO (PBOO) in female rats was established to explore the variation in bladder wall ECM proteins under PBOO conditions with antimuscarinic agent administration. Methods: Rats were randomly divided into three groups: sham, PBOO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Previous work by us (22,29), and others (10,11,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) have shown the crucial role of ECM in PBO pathology.…”
Section: Discussionmentioning
confidence: 85%
“…Previous work by us (22,29), and others (10,11,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) have shown the crucial role of ECM in PBO pathology.…”
Section: Discussionmentioning
confidence: 85%
“…After MSC treatment of PBOO rats, the bladder had physiological benefits, and Tgfb, Hif1a, Hif3a, Mtor, Col1, and Col3 were downregulated. Yang et al demonstrated that tolterodine, a drug used to delay PBOO progression, can reduce collagen volume in the bladder wall of PBOO [10]. Moreover, tolterodine also induced MMP7, ITGA4, ITGB2, TIMP1, and FN1, which may be a mechanism of tolterodine for PBOO treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There are rare microarray and NGS studies on PBOO-induced gene expression. Yang et al tried to investigate the gene expressions of ECM proteins, receptors, and metabolism regulators in a rat PBOO model [10]. However, only few differentially expressed genes (DEGs) were significantly decreased in the PBOO group compared with the sham group.…”
Section: Introductionmentioning
confidence: 99%
“…The animal experiments were done in adherence with the National Institutes of Health Guidelines and approved by the West China Hospital Committee on Animal Care. Based on our previous study, female rats (220–250 g) were subdivided into sham‐operated and PBOO groups, with five rats in each group 20 . Briefly, after anesthesia, a catheter with an outer diameter of 1 mm was placed into the urethra of the rat, and the bladder neck was ligated using 4‐0 wires to establish PBOO.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our previous study, female rats (220-250 g) were subdivided into sham-operated and PBOO groups, with five rats in each group. 20 Briefly, after anesthesia, a catheter with an outer diameter of 1 mm was placed into the urethra of the rat, and the bladder neck was ligated using 4-0 wires to establish PBOO. The sham-operated group underwent the same procedure but without urethral ligation.…”
Section: Microarray Data Of the Obstructed Bladdermentioning
confidence: 99%